Solvent-free synthesis of polyhydroquinoline and 1, 8-dioxodecahydroacridine derivatives through the Hantzsch reaction catalyzed by a natural organic acid: A green method. Issue 12 (18th June 2017) - Sehout, Imène; Boulcina, Raouf; Boumoud, Boudjemaa; Boumoud, Taous; Debache, Abdelmadjid
ABSTRACT: Solvent-free and high yielding one-pot synthesis of 1, 8-dioxodecahydroacridine and polyhydroquinoline derivatives have been described through Hantzsch condensation of various aldehydes, ammonium acetate with cyclic 1, 3-dicarbonyl compounds and ethyl acetoacetate in a very simple, efficient, and environmentally benign method using ascorbic acid as a nontoxic organocatalyst. GRAPHICAL ABSTRACT: